The California Nautical School: What it has Done and What it is Doing to Train Young Men to Become Merchant Marine Officers - Topp, Captain Emile (The Log)
Under varied conditions of wind, weather and temperature the training ship California State recently completed her first cruise, a service test of some 22,000 miles of steaming. She left San Francisco last December, circled South America to New York and returned via the Canal at the end of May. Large enough to be comfortable, small enough to be economical,dependable and sea Cpt.Emile Topp, worthy, it has been demonstrated that the vessel is well suited for her purpose.